Predictors of Smartphone usages among Management Students - Neha Yadav (Dr. Chinmay Pandya, 2019)
Technology becomes an integrated part of today's life and it has significant changed cultural norms of behavior of individual. Most popular application of the technology is the smartphone and it has impacted the students' behavior. The main objective of this research is to examine the predictors of Smartphone usages among Management Students. Following an exploratory approach, a systematic review of the relevant studies has been done to provide an integrated view of the fragmented literature. Convenience sampling technique was used to collect the response of 225 students from the population. Descriptive statistical technique was used for data analysis. Factor analysis has performed to check the outcome variables for investigation through SPSS 20.0. The result shows that there are three main predictors of smartphone usages among management students - sharing & collaboration, Learning, and Creativity & innovation.